Assistive Technology in Education: Screen Magnifier - Zelly putriani; Robi Kurniawan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
Technology, which basically helps human do things easier, has also emerged in helping learners perform a better learning. This descriptive study explores the screen magnifier as assistive technology in education which is installed in many electronic devices for visual assistance. It also pinpoints how the technology works, characteristics of the students who use the technology, issues of the technologies use in the classroom (including costs). The study indicates that screen magnifier is crucially important for low vision students because most learning activities require a lot of intensive eye sight. Furthermore, the users may find screen magnifier easy to install and to use. Besides that, this study suggests that students also get accommodation besides using Screen Magnifier individually in the classrooms.